2010
DOI: 10.3109/10611861003801834
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing chemotherapeutic drug inhibition on tumor growth by ultrasound: anin vivoexperiment

Abstract: An in vivo study on enhancing epirubicin hydrochloride (EPI) inhibition on tumor growth by ultrasound (US) was reported. Five-week-old male nude mice were used and HL-60 cells were s.c. (subcutaneous injection) inoculated in axilla of these mice. Six groups were designed and five consecutive treatments were applied to investigate the inhibition on tumor growth and body weight growth. US applied locally to the tumor resulted in a substantially increased drug uptake in tumor cells. The inhibition on tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…, increased apoptotic activity and cell death) when comparing tumors treated with US-stimulated drug delivery compared to drug alone. When exploring other in vivo applications of US-stimulated drug delivery, previously reported methods analyzed secondary indicators of tumor response to treatment by measuring size and evaluating histological results post-mortem (Zhao, Lu 2011). MRI-based measures have also shown to be effective in confirming US-stimulated drug delivery through the blood-brain barrier (Kinoshita, McDannold 2006, McDannold, Arvanitis 2012, O'Reilly, Waspe 2012, Treat, McDannold 2012).…”
Section: Discussionmentioning
confidence: 99%
“…, increased apoptotic activity and cell death) when comparing tumors treated with US-stimulated drug delivery compared to drug alone. When exploring other in vivo applications of US-stimulated drug delivery, previously reported methods analyzed secondary indicators of tumor response to treatment by measuring size and evaluating histological results post-mortem (Zhao, Lu 2011). MRI-based measures have also shown to be effective in confirming US-stimulated drug delivery through the blood-brain barrier (Kinoshita, McDannold 2006, McDannold, Arvanitis 2012, O'Reilly, Waspe 2012, Treat, McDannold 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant in vivo analogue of this in vitro approach requires the direct injection of MBs into tumor tissue. With this approach, it has been reported that combined USMB-drug treatments can result in growth inhibition, though significantly enhanced antitumor effects relative to drug only or USMB-only groups were not found [11], [12]. Studies using systemically (intravenously) injected MBs, the current clinically approved method for introducing agents into the body, have also been conducted with rationale of enhancing drug delivery into tumor tissue by increasing extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…In brain tumors, results have begun to emerge showing improved therapeutic effects by employing ultrasound stimulated microbubbles (USMB) with liposomal drug formulations under conditions that produce enhanced drug extravasation [6][8]. Outside the brain, results have recently been obtained indicating that the use of USMBs with anticancer agents can result in improved delivery and therapeutic effects relative to the drug only case [9][12]. With the exception of brain tumors, where the blood-brain-barrier presents a significant drug delivery obstacle, it must also be considered that in many circumstances the penetration of antitumor agents into tumor tissue is not inhibited by their inability to extravasate from the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of ultrasound waves with MBs may cause oscillation and cavitation of the bubbles and lead to the rupture of vascular walls. [14][15][16] For overcoming the difficulties of drug delivery posed by vascular walls, US sonication in the presence of MBs can produce ruptured openings to increase vascular permeability of sonicated tissues and permit a specific and effective cellular uptake. [17][18][19][20] Studies have recently demonstrated that ultrasoundmediated chemotherapeutics with MBs showed promising potential for animal tumor treatment.…”
Section: Introductionmentioning
confidence: 99%